PERAN PEREMPUAN DALAM DAKWAH KONTEMPORER - Lia Wati Harahap (Program Studi Komunikasi Penyiaran Islam Fakultas Dakwah dan Komunikasi, 2022)
This article aims to find out the role of women in contemporary da'wah, where women in Islam have the same rights in preaching but that distinguishes the level or dose. Islam positions women in this very respectable position because women have tasks that cannot be done by men such azs conceiving, giving birth and breastfeeding all of which risk their lives in their application. In this article discussed there are three roles of women the first role of women in the Islamic view of women occupying a respectable and also noble position. Islam does not distinguish men from women for da'wah affairs such as ber amar ma'ruf nahi mungkar. Both related to the role of women in the household has a complex role that broadly the role is as a mother, as a wife and as a society. The three roles of women in da'wah are in accordance with the level of their ability in preaching ma'ruf nahi mungkar, can preach at home with their families, can preach on the road, in the market or also through social media which is all done to preach ma'ruf nahi mungkar